Invisible population the place of the dead in East Asian megacities - Aveline-Dubach, Natacha; ebrary, Inc. (Lanham : Lexington Books, 2012)
"Provides new information on funerary practices in East Asia's largest cities in which spatial constraints and the secularization of lifestyles are driving innovation. It reveals common trends in Japan, China and Korea, and addresses emerging challenges such as urban sustainability and growing social inequities."--Publisher's description.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Funeral rites and ceremonies -- East Asia -- History -- 20th century; Funeral rites and ceremonies -- East Asia -- History -- 21st century; Death care industry -- Social aspects -- East Asia -- History -- 20th century; Death care industry -- Social aspects -- East Asia -- History -- 21st century; City and town life -- East Asia -- History -- 20th century; City and town life -- East Asia -- History -- 21st century; Electronic books